Diagnostic yield of candidate genes in an Australian corneal dystrophy cohort. Issue 10 (19th August 2022) - Souzeau, Emmanuelle; Siggs, Owen M.; Mullany, Sean; Schmidt, Joshua M.; Hassall, Mark M.; Dubowsky, Andrew; Chappell, Angela; Breen, James; Bae, Haae; Nicholl, Jillian; Hadler, Johanna; Kearns, Lisa S.; et al.
Abstract: Corneal dystrophies describe a clinically and genetically heterogeneous group of inherited disorders. The International Classification of Corneal Dystrophies (IC3D) lists 22 types of corneal dystrophy, 17 of which have been demonstrated to result from pathogenic variants in 19 identified genes. In this study, we investigated the diagnostic yield of genetic testing in a well‐characterised cohort of 58 individuals from 44 families with different types of corneal dystrophy. Individuals diagnosed solely with Fuchs endothelial corneal dystrophy were excluded. Clinical details were obtained from the treating ophthalmologist. Participants and their family members were tested using a gene candidate and exome sequencing approach. We identified a likely molecular diagnosis in 70.5% families (31/44). The detection rate was significantly higher among probands with a family history of corneal dystrophy (15/16, 93.8%) than those without (16/28, 57.1%, p  = .015), and among those who had undergone corneal graft surgery (9/9, 100.0%) compared to those who had not (22/35, 62.9%, p  = .041). We identified eight novel variants in five genes and identified five families with syndromes associated with corneal dystrophies. Our findings highlight the genetic heterogeneity of corneal dystrophies and the clinical utility of genetic testing in reaching an accurate clinical diagnosis. Abstract : Genetic testing in 58 individuals from 44 families with a clinical diagnosis of corneal dystrophy yielded a molecular diagnosis in 70.5% of families using a gene candidate and exome sequencing approach.